Character Building Through Fitrah Based Education In The Era Of Society 5.0 - Haris, Didik Nur (Universitas Islam Negeri Raden Intan Lampung, 2023)
The era of the industrial revolution 4.0 has given birth to major changes in the 21st century marked by the development of the Internet of Things (IoT), Artificial Intelligence (AI) and Big Data. This revolution has impacted all aspects of life, including social, economic, cultural, political and educational, with the emergence of a world order that is full of volatility, uncertainty, complexity and ambiguity. The idea of the era of society 5.0 is a new hope for the birth of humanist technological progress where humans are the center of a technology-based society for a more meaningful and balanced life. This study is a liberary research which states that the approach to the educational process based on fitrah and basic human potential is more likely to create a natural, adaptive and comfortable learning process through five models of fitrah-based education approaches, namely character-based education, collaboration-based education, project-based education, talent-based education and role model-based education.